STRENGTHENING RELIGIOUS CHARACTER BASED ON PAI SUBJECTS IN MA'ARIF NU JUNIOR HIGH SCHOOL STUDENTS KEMRANJEN BANYUMAS - Ervin Arifuddin; A. Jauhar Fuad; Yusuf Aspidin; M. Jamalun Nizar (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
The purpose of this study was to describe and analyze religious values ​​based on PAI subjects and teachers' strategies in strengthening religious values. The approach in this research is qualitative and the type is phenomenology. The data analysis technique uses the Spradley model where the entire research process consists of: descriptive observation, domain analysis, focused observation, taxonomic analysis, selected observations, component analysis, and ends with theme analysis. The process can be simplified into four stages, namely domain, taxonomy, component, and theme analysis. The results of the study stated that first, religious values ​​based on PAI subjects at SMP Ma'arif NU 2 Kemranjen synergize with local content subjects, namely aswaja and fiqh. This integration is a strategic form of awareness of teachers and managers of educational institutions in preparing students to know, understand, live, have faith, be pious, have noble character, practice Islamic teachings from the main source of the holy book al-Qur'an and al-Hadith. The strategy used by the teacher is a studentcentered approach. The methods that often appear are exemplary and habituation considering that these two things are often applied in Islamic boarding schools. This is supported by good teacher competence so that they are able to make religious values ​​successfully absorbed by students and appear in daily behavior.